Laser-Induced Graphene-Based Wearable Epidermal Ion-Selective Sensors for Noninvasive Multiplexed Sweat Analysis - Jianjun Liao; Xiangya Zhang; Zihan Sun; Hande Chen; Jian Fu; Hewei Si; Chengjun Ge; Shiwei Lin (Biosensors, 2022)
Wearable sweat sensors are a rapidly rising research area owing to their convenience for personal healthcare and disease diagnosis in a real-time and noninvasive manner. However, the fast and scalable fabrication of flexible electrodes remains a major challenge. Here, we develop a wearable epidermal sensor for multiplexed sweat analysis based on the laser-induced graphene (LIG) technique. This simple and mask-free technique allows the direct manufacturing of graphene electrode patterns on commercial polyimide foils. The resulting LIG devices can simultaneously monitor the pH, Na+, and K+ levels in sweat with the sensitivities of 51.5 mV/decade (pH), 45.4 mV/decade (Na+), and 43.3 mV/decade (K+), respectively. Good reproducibility, stability, and selectivity are also observed. On-body testing of the LIG-based sensor integrated with a flexible printed circuit board during stationary cycling demonstrates its capability for real-time sweat analysis. The concentrations of ions can be remotely and wirelessly transmitted to a custom-developed smartphone application during the period in which the sensor user performs physical activities. Owing to the unique advantages of LIG technique, including facile fabrication, mass production, and versatile, more physiological signals (glucose, uric acid, tyrosine, etc.) could be easily expanded into the LIG-based wearable sensors to reflect the health status or clinical needs of individuals.